2003
DOI: 10.4141/a02-111
|View full text |Cite
|
Sign up to set email alerts
|

Savaging behaviour in gilts and sows

Abstract: . 2003. Savaging behaviour in gilts and sows. Can. J. Anim. Sci. 83: 819-821. This study investigated the effects of parity, prior experience, and environmental conditions on the incidence of savaging on seven commercial farms. Results indicated that 3.40% of gilts and 1.22% of sows killed one or more piglets (P < 0.05). Fourteen percent of sows that savaged as gilts also savaged during their second farrowing, compared to 0.8% of sows that had not previously savaged. The incidence of savaging was similar among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Savaging of piglets is observed both in gilts and sows and is considered to be an abnormal maternal response (Ahlström et al, 2002). Analysing data of seven commercial farms, Harris et al (2003) reported that 3.40% of gilts and 1.22% of sows killed one or more piglets. Cronin et al (1996) compared piglet mortality in a conventional crate and a pair-pen loose housing system for two sows and found that more piglets were savaged in the crate system (2.4% vs. 1.4%).…”
Section: Savaging Of Piglets By Lactating Gilt/sowmentioning
confidence: 99%
“…Savaging of piglets is observed both in gilts and sows and is considered to be an abnormal maternal response (Ahlström et al, 2002). Analysing data of seven commercial farms, Harris et al (2003) reported that 3.40% of gilts and 1.22% of sows killed one or more piglets. Cronin et al (1996) compared piglet mortality in a conventional crate and a pair-pen loose housing system for two sows and found that more piglets were savaged in the crate system (2.4% vs. 1.4%).…”
Section: Savaging Of Piglets By Lactating Gilt/sowmentioning
confidence: 99%
“…Savaging is much more common in first time mothers than in experienced sows (English et al, 1977;Harris et al, 2003) but the true incidence of potentially infanticidal behaviour is probably under-estimated due to lack of data. On commercial farms and many experimental studies, savaging is used to describe the interactions between dam and piglet that result in death of the piglet, rather than offspring-directed aggression that does not result in mortality.…”
Section: Challenges With Farrowingmentioning
confidence: 99%
“…On commercial farms and many experimental studies, savaging is used to describe the interactions between dam and piglet that result in death of the piglet, rather than offspring-directed aggression that does not result in mortality. The percentage of gilts that savage piglets to death has been quoted in various studies as 3.4% (Harris et al, 2003), 8.1% (Marchant-Forde, 2002) and 18.7% (Cronin and Smith, 1992). These differences can probably be explained in part by the fact that the Harris et al (2003) study is reporting a large farmerentered database using crates, whereas the other two studies are reporting relatively small scale experimental studies using a mixture of open pens and crates.…”
Section: Challenges With Farrowingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, experience with primiparous sows is important in relation to commercial adoption of the MS system. Compared with multiparous animals, primiparous animals may show more savaging behaviour of their new-born piglets (Harris et al, 2003;Chen et al, 2008), and specifically in an MS system, they may be more susceptible to teat damage related to cross-suckling , and to aggression-related skin lesions due to a lower dominance rank (Hultén et al, 1995b). Moreover, induction of lactational oestrus and ovulation may be less effective in primiparous animals (Hultén et al, 1995a;Soede et al, 2012).…”
Section: Future Optimisation Of the Ms Systemmentioning
confidence: 99%